Low temperature direct wafer bonding of GaAs to Si via plasma activation - Xu, D. W. (2014)
The present work seeks to demonstrate the elegance and simplicity of monolithic integration via plasma-activated direct wafer bonding. Two-inch gallium arsenide and silicon wafers were directly bonded through argon plasma activation. The highest specific bond energy was found for plasma conditions of 30 s, 120 mTorr, and 200 W, followed by low temperature annealing at 140 °C, and was 478 mJ/m2. Through this process, a processed silicon integrated circuit could be integrated with optoelectronics gallium arsenide on a wafer scale.